2020
DOI: 10.1097/sla.0000000000004040
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Body Composition Analysis on Chest Computed Tomography Predicts Hospital Length of Stay and Complications After Lobectomy for Lung Cancer

Abstract: Objective: To investigate the impact of thoracic body composition on outcomes after lobectomy for lung cancer Summary and Background Data: Preoperative identification of patients at risk for adverse outcomes permits treatment modification. The impact of body composition on lung resection outcomes has not been investigated in a multicenter setting. Methods: A total of 958 consecutive patients undergoing lobectomy for lung cancer at 3 centers from 2014 to 2017 were retrospectively analyzed. Muscle and adipose ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
1
20
1
Order By: Relevance
“…Similar to prior studies, pulmonary function tests showed no significant effect 13 . As previously demonstrated, age was not associated with survival, highlighting that mortality risk is not so much defined by chronologic, but morphologic age 16,34–36 …”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Similar to prior studies, pulmonary function tests showed no significant effect 13 . As previously demonstrated, age was not associated with survival, highlighting that mortality risk is not so much defined by chronologic, but morphologic age 16,34–36 …”
Section: Discussionsupporting
confidence: 83%
“…The choice of analyzed thoracic vertebral levels in this study was informed by prior reports and our own institutional experience 13,16,23 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 25 ] In addition, computed tomographic thoracic scans that are performed preoperatively may precisely detect patients with low muscle mass and fatty muscle infiltration which are predictive of mortality, major complications and prolonged hospital stay after colorectal surgery and lung cancer resection. [ 26 27 ]…”
Section: Preoperative Patient Nutritional Conditionmentioning
confidence: 99%